Improvement of formal methods of analysis of the environment of the organization by detailed ranking of factors - Shtuchnyy, V. H.; Nechiporenko , Ya. Ye. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2018)
Rapid changes in the current economic realities of the functioning of enterprises determine the growing importance of strategic management in general, and in particular, an accurate analysis of their external and internal environment. The article proposes the improvement of such formal methods of research of the organization environment as a matrix of possibilities, a matrix of threats and a profile analysis by detailed ranking of the factors of the organization environment regarding their explored qualities, which significantly increases the information content of these methods. A step-by-step sequence of actions for constructing the matrix of possibilities, the matrix of threats, the profile analysis according to reviewed methods is given. Attention is paid to the differences in the construction of the matrix of possibilities and the  matrix of threat according to a well-known approach based on a predefined matrix form (nine or twelve fields) and the approach proposed by the authors, the main ones being the individual matrix form for an individual organization, a clear ranking of factors by the degree of their significance and the allocation of fields at the crossroads of identical numbers of factors as those that carry a semantic load. The main difference of the authors' approach to the  profile analysis of the organization environment is a more gradual grading of the integral assessment of the degree of importance of environmental factors, and if the number of factors is n, then the integral estimate of the degree of importance of the environmental factor can now range from to .Specification of the construction methods of the matrix of opportunities, the matrix of threats, the profile analysis allows to analyze the organization environment more thoroughly. The article also shows the practical use of refined methods on the example of analysis of the external and internal environment of the functioning of the TPK "Budkonstruktsii" LLC.